Corporate governance in Serbian family-owned companies: Idle opportunities - Jevremović-Petrović Tatjana (Anali Pravnog Fakulteta u Beogradu)
This paper aims to contribute to legal research on family-owned companies, focusing on Serbian law. This company type is the focus of Part Two of the Serbian Corporate Governance Code, which contains various specific corporate governance mechanisms, such as succession plans, family general meetings, family councils, and family protocols and recommendations aiming to achieve responsibility, transparency, continuity, efficiency, and fair treatment of all shareholders. The paper presents existing possibilities and explores whether a specific Serbian corporate governance regime dedicated to family-owned companies can be accommodated into a general company law regime. This paper aims to further promote the use of specific mechanisms designed for family-owned companies, paying particular attention to the importance of drafting family protocols. These protocols can regulate not only typical corporate governance issues but are also suitable to include the family-owned company's vision and mission as a sustainable, balanced, and long-term viable business organization.